Treaty Department and successors : General Correspondence from 1906 : Mexico (Public Record Office, 1960)
Foreign Office 372 (class "FO 372") "contains correspondence, etc., of the Treaty Department and its successors [1906-1967, 8,213 files and volumes], including the Prize Court Department, 1914 to 1920, and the Dominions Information Department, 1926 to 1928. Subjects covered include treaty correspondence with other countries; shipping claims against Russia and Japan arising from the Russo-Japanese war; honours and decorations; territorial waters; extradition treaties; nationality; consular and diplomatic appointments; prize courts; diplomatic privileges; civil procedure; marriage regulations; deportation agreements and various royal matters, including state and royal visits."--Online catalog of the Great Britain National Archives.